2021
DOI: 10.1007/s00425-020-03522-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative RNA-Seq analysis reveals genes associated with masculinization in female Cannabis sativa

Abstract: Main conclusion Using RNA profiling, we identified several silver thiosulfate-induced genes that potentially control the masculinization of female Cannabis sativa plants. Abstract Genetically female Cannabis sativa plants normally bear female flowers, but can develop male flowers in response to environmental and developmental cues. In an attempt to elucidate the molecular elements responsible for sex expression in C. sativa plants, we developed gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 64 publications
1
38
1
Order By: Relevance
“…However, it is not possible to discriminate these isomers with the LC stationary phase used in this study. This is the first report of the upregulation of OPDA in Cannabis flowers and given that APA-and auxin-related genes are directly implicated in sex expression, [20,51,55] this compound may represent a molecule of interest for further investigation.…”
Section: Dams Associated With Sexual Phenotypementioning
confidence: 80%
“…However, it is not possible to discriminate these isomers with the LC stationary phase used in this study. This is the first report of the upregulation of OPDA in Cannabis flowers and given that APA-and auxin-related genes are directly implicated in sex expression, [20,51,55] this compound may represent a molecule of interest for further investigation.…”
Section: Dams Associated With Sexual Phenotypementioning
confidence: 80%
“…It may be the result of altered regulation of synthesis enzymes, for example the upregulation of THCA synthase or CBCA synthase (Laverty et al, 2019). A previous study found over 10,000 genes are differentially expressed upon masculinization of female plants (Adal et al, 2021), but it is not clear how these genes are related to phytocannabinoid expression in the fertilized female plant. A donor-dependent effect was also detected in the specific increase in the Eudesmol family (α-, β-, and γ-Eudesmol) components, which were highly increased in the THC-rich female upon fertilization by the THC-rich male plant (Figure 6A) and a parallel specific increase in Linalool in the CBD-rich female fertilized by the induced male (Figure 6B).…”
Section: Discussionmentioning
confidence: 98%
“…Low-quality reads (>10% Ns or a PHRED score <10 for at least 50% of bases), and those containing adaptor sequences were removed from the resultant reads using an internally developed script. The expression levels of mapped-paired reads were normalized as reads per kilobase per million mapped reads (RPKM), with the CLC RNA-Seq analysis tool ( Adal et al, 2021 ). The normalized reads were then used for the differential expression analyses in two groups.…”
Section: Methodsmentioning
confidence: 99%